2021
DOI: 10.1039/d1mh00812a
|View full text |Cite
|
Sign up to set email alerts
|

A linear scaling law for predicting phase transition temperature via averaged effective electronegativity derived from A2M3O12-based compounds

Abstract: Chemical flexibility of A2M3O12-based compounds enables design of materials with versatile functionalities such as ferroelastic switching, ion conduction and negative thermal expansion (NTE) above ferroelastic transition temperature (Tt), promising for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Based on this, the concepts of average atomic volume (AAV) and average effective electronegativity (AEE) have been successfully proposed to qualitatively or quantitatively study the relationships of the CNTE with AAV and phase transition temperature with AEE for both cyanides and oxides. 19,20 These relationships are proved to be universal and can well explain some newly discovered NTE oxides, such as Cu 2 P 2 O 7 . 21 More importantly, in view of their application with a desired CNTE, we hoped that multiple NTE mechanisms can be mixed-introduced to the materials in tailoring the CNTE effectively.…”
Section: ■ Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Based on this, the concepts of average atomic volume (AAV) and average effective electronegativity (AEE) have been successfully proposed to qualitatively or quantitatively study the relationships of the CNTE with AAV and phase transition temperature with AEE for both cyanides and oxides. 19,20 These relationships are proved to be universal and can well explain some newly discovered NTE oxides, such as Cu 2 P 2 O 7 . 21 More importantly, in view of their application with a desired CNTE, we hoped that multiple NTE mechanisms can be mixed-introduced to the materials in tailoring the CNTE effectively.…”
Section: ■ Introductionmentioning
confidence: 81%
“…Generally speaking, the CNTEs of open framework materials depend strongly on their crystal structure, lattice symmetry, structural flexibility, and electronegativity of atoms. Based on this, the concepts of average atomic volume (AAV) and average effective electronegativity (AEE) have been successfully proposed to qualitatively or quantitatively study the relationships of the CNTE with AAV and phase transition temperature with AEE for both cyanides and oxides. , These relationships are proved to be universal and can well explain some newly discovered NTE oxides, such as Cu 2 P 2 O 7 . More importantly, in view of their application with a desired CNTE, we hoped that multiple NTE mechanisms can be mixed-introduced to the materials in tailoring the CNTE effectively. , Meanwhile, this is also a fundamental work to discover new NTE physics and understand the synergistic effect of different NTE mechanisms theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all materials expand when heated, so negative thermal expansion (NTE) in which the volume shrinks on heating has always attracted much attention due to the rich underlying physics and great potential applications. [1][2][3][4] The presence of NTE materials offers a promising possibility to design materials with special thermal properties, such as zero thermal expansion, which are valuable in precision optics, thermo-mechanical actuators and space applications. 5 So far, a large number of NTE materials have been identified such as alloy, oxides, fluorides, cyanides, Prussian blue analogues (PBAs), metal-organic frameworks, manganese nitrogen compounds, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] NTE in open-framework materials, such as ReO 3 , AMO 5 , AMO 7 AMO 8 , AMO 12 , and ScF 3 , always involves phonon-related transverse cooperative vibrations. 2,[12][13][14] The NTE behavior in these cases is caused by the thermal motion of oxygen atoms transverse to M-O-M linkages (or of fluorine atoms transverse to Sc-F-Sc linkages in ScF 3 ). 15,16 The exceptionally large NTE behavior in Zn(CN) 2 is presumably also related to transverse thermal motion of both C and N perpendicular to Zn-C-N-Zn linkage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in nature, positive thermal expansion (PTE) is more universal than negative thermal expansion (NTE), while for flexible open framework structure materials, the transverse vibration of bridging atoms produces enough dragging force to drive the polyhedra connected with the bridging atom coupling rotation. The transverse vibration of the bridging atom corresponding to low frequency phonons leads to NTE. In ZrW 2 O 8 , it is reported that the low energy vibrational modes that lead to NTE involve the correlated rotations of ZrO 6 octahedra that produce large (111) translations of the WO 4 tetrahedra …”
Section: Introductionmentioning
confidence: 99%